Isolation, characterization and anti-inflammatory activity of compounds from the Vernonia amygdalina - Olubunmi Atolani; Mohammed Abubakar Usman; Jamiu Opeyemi Adejumo; Adedamola Elizabeth Ayeni; Olamilekan Joseph Ibukun; Adeola T. Kola-Mustapha; Ngaitad S. Njinga; Luqman A. Quadri; Emmanuel O. Ajani; Tajudeen O. Amusa; Moji T. Bakare-Odunola; Adenike T. Oladiji; et al. (Heliyon, 2024)
The need to explore the abundance of natural products cannot be overemphasized particularly in the management of various disease conditions. In traditional medical practice, Vernonia amygdalina has been widely adopted in the management of various inflammatory disorders. The objective of this investigation was to isolate the bioactive principles from the stem-bark and root of V. amygdalina and assess the anti-inflammatory (in vitro) activity of both the crude extracts and the isolated compounds. Following extraction with the methanol, the extract was subjected to gravity column chromatography and the resultant fractions was further purified to obtained pure compounds. The structural elucidation of the compounds were based on data obtained from 1H to 13C nuclear magnetic resonance (NMR) spectroscopies as well as fourier transform infrared (FT-IR). Using diclofenac as a control drug, the albumin denaturation assay was used to determine the in vitro anti-inflammatory activity of the extracts and isolates. Three distinct compounds characterized are vernoamyoside D, luteolin-7-α-o-glucuronide, and vernotolaside, a new glycoside. When compared to diclofenac, which has an IC50 of 167.8 μg/mL, luteolin-7-α-o-glucuronide, vernoamyoside D, and vernotolaside all showed significant inhibitions with respective IC50 values 549.8, 379.5, and 201.7 μg/mL. Vernotolaside is reported for the first time from the root. The assertion that the plant is used in traditional medicine for the management of inflammatory disorder is somewhat validated by the confirmation of the existence of the compounds with the biochemical actions. Further validation of the isolated compounds would be required in animal studies.